Kegiatan Pendistribusian Zakat Produktif Pemberdayaan UMKM di LAZIZMU Kabupaten Gresik - Ayu Rahmatul Ainiyah; Airlangga Bramayudha (Journal of Islamic Management, 2021)
This study aims to determine the form of productive zakat distribution activities for empowering MSMEs in LAZISMU Gresik district and determine several factors that influence the effectiveness of these activities. This research used descriptive qualitative reseacrh method. Qualitative descriptive was used to descriptive and examine in depth the form of productive zakat distribution activites for empowering MSMEs in LAZISMU district and the factors that influenced the effectiveness of these activities. Them, the data collection technique was carried out by means of interviews, observations, and documentation. The results of this study were as follows. First, the activity that moved to increase community potentiol in the Economic field. There were certain rules that had to be followed In this activity. Among them were the distribution system, the form of zakat distribution, the distribution pattern, the criteria for productive zakat recipient groups to the stages or procedure for disturbing zakat potential beneficiaries. Second, there were several factors that influenced the productive zakat distribution activities for the empowerment of MSMEs in LAZISMU Gresik regency. Among them were goal setting, human resource search and utilization, achievement environment, communication process, leadership and decision making, and innovation.